2020
DOI: 10.1039/d0ra00119h
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic defect engineered Janus MoSSe sheet as a promising photocatalyst for water splitting

Abstract: The Janus MoSSe sheet has aroused significant attention due to its band edge position and intrinsic dipole moment, making it a strong candidate for water splitting photocatalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…However, the adsorption energy can be increased to -0.321 eV if H 2 O adsorbs on the S-vacancy site. [121] This tendency can be found also for NO, NO 2 or other molecules, suggesting a critical role for Se and S/Se vacancies in controlling the sensitivity of MoSSe for molecular adsorption and related gas-sensing applications. Table 4.…”
Section: Gas Sensing Devicesmentioning
confidence: 90%
“…However, the adsorption energy can be increased to -0.321 eV if H 2 O adsorbs on the S-vacancy site. [121] This tendency can be found also for NO, NO 2 or other molecules, suggesting a critical role for Se and S/Se vacancies in controlling the sensitivity of MoSSe for molecular adsorption and related gas-sensing applications. Table 4.…”
Section: Gas Sensing Devicesmentioning
confidence: 90%
“…[ 74–76 ] Second, the defects in low‐dimensional compounds can easily migrate to form interstitials due to the broad space of the interlayer or interchain, rather than antisites and substitutions. [ 77,78 ] Third, the crystal framework with high dimensionality facilitates the carrier migration along different orientations. While in the low‐dimensional materials, high anisotropy of carrier mobility and conductivity are hardly negligible.…”
Section: Pb‐free Ns2‐cation‐containing Semiconductors For Optoelectronic Applicationsmentioning
confidence: 99%
“…20 The intrinsic S or Se vacancies will adsorb protons better than the basal planes thereby significantly improving the efficiency of HER on the surfaces of 2D J-MoSSe, as shown by both experiment and theoretical results. 20,25,26 The S or Se vacancies naturally exist on the surfaces of 2D J-MoSSe when prepared by CVD, similar to MoS2 which contains a noticeable fraction of S vacancies when prepared by either mechanical exfoliation or CVD. 27,28 Researchers also demonstrated that adsorbed transition-metals on 2D J-MoSSe will improve the reactant adsorption as well as enlarge the optical absorption range.…”
Section: Introductionmentioning
confidence: 97%